Optimal taxation, social contract and the four worlds of welfare capitalism - Olivier Bargain; Amedeo Spadaro (University College Dublin, UCD School of Economics, 2008)
Drawing from the formal setting of the optimal tax theory (Mirrlees 1971), the paper identifies the level of Rawlsianism of some European social planner starting from the observation of the real data and redistribution systems and uses it to build a metric that allows measuring the degree of (dis)similarity of the redistribution systems analyzed. It must be considered as a contribution to the comparative research on the structure and typology of the Welfare State (Esping-Andersen, 1990). In particular we consider the optimal taxation model that combines both intensive (Mirrlees) and extensive (Diamond) margins of labor supply, as suggested by Saez (2002) in order to assess the degree of decommodification of seven European welfare systems. We recover the shape of the social welfare function implicit in taxbenefit systems by inverting the model on actual effective tax rates, as if existing systems were optimal according to some Mirrleesian social planner. Actual distributions of incomes before and after redistribution are obtained using a pan-European tax-benefit microsimulation model. Results are discussed in the light of standard classifications of welfare regimes in Europe. There appears to be a clear coincidence of high decommodification and high Rawlsianism in the Scandinavian, social-democratically influenced welfare states (Denmark). There is an equally clear coincidence of low decommodification and utilitarianism in the Anglo-Saxon liberal model (UK) and in the Southern European welfare states (Italy and Spain). Finally, the Continental European countries (Finland, Germany and France) group closely together in the middle of the scale, as corporatist and etatist.
hdl:10197/969
Keywords: H11; H21; D63; C63; 330; Optimal income taxation; tax-benefit policy; microsimulation; comparative social policy analysis; welfare state models